2012
DOI: 10.1111/j.1476-4431.2012.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Compartment syndrome: pathophysiology, clinical presentations, treatment, and prevention in human and veterinary medicine

Abstract: CS is a complex clinical condition where increased pressure within a compartment can cause significant adverse effects within the compartment as well as throughout the body. Systemic inflammatory responses and local ischemia-reperfusion elements can contribute to the detrimental effects seen in CS. This cascade of events results in increased mortality rates and contributes to the development of CS elsewhere. A better understanding of CS will help veterinarians improve patient care and outcome. Future studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 76 publications
0
56
0
1
Order By: Relevance
“…; Nielsen and Whelan ). In a clinical setting, however, these tools may not be available and therefore diagnosis is usually based on history and clinical signs consistent with compartment syndrome (Rorabeck and McGee ; Nielsen and Whelan ).…”
Section: Introductionmentioning
confidence: 99%
“…; Nielsen and Whelan ). In a clinical setting, however, these tools may not be available and therefore diagnosis is usually based on history and clinical signs consistent with compartment syndrome (Rorabeck and McGee ; Nielsen and Whelan ).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in IAP to >20 mm Hg has a profound effect on cardiac output and urinary output . It had been assumed that the decrease in urinary output is due to a decrease in cardiac output, which in turn results from decreased venous return . However, Harman et al reported that maintenance of cardiac output at a normal level did not appear to prevent kidney failure in an experimental model of elevated IAP.…”
Section: Discussionmentioning
confidence: 99%
“…A sustained increase in intra‐abdominal pressure (IAP) can cause intra‐abdominal hypertension (IAH) and abdominal compartment syndrome (ACS), which contributes significantly to increased morbidity and mortality in critically ill people . The increased pressure within the abdominal cavity can adversely affect normal perfusion and function in the surrounding tissues, and eventually this process can lead to physiologic dysfunction and multiple organ failure . In veterinary medicine, there have been a few reports of IAH and ACS having multiple negative systemic effects .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Definitive diagnosis can be achieved by measuring intracompartmental pressure either using invasive (manometry) or noninvasive (near infrared spectroscopy) techniques. However, it is generally agreed that clinical signs indicative of compartment syndrome warrant intervention without confirmation (Nielsen and Whelan 2012). If left untreated, compartment syndrome may result in loss of the limb, in which case amputation is required.…”
Section: Peer-reviewed Correspondencementioning
confidence: 98%